Power, trust and control: The interaction of political behaviours in accounting-based ERP system implementation processes. Issue 4 (5th November 2018) - Hassan, Mostafa Kamal; Mouakket, Samar
Abstract : Purpose: The purpose of this paper is to explore political behaviours associated with the implementation of an enterprise resource planning (ERP) system in a public service organisation from an emerging market country, the United Arab Emirates (UAE). Design/methodology/approach: The authors' theoretical framework is based on the notions of trust, agent reflexivity, ontological security, routines, control and power proposed by Giddens (1984, 1990). The authors explore how the political behaviour of organisation members emanates from the introduction of an ERP system (particularly its accounting modules), and how the interaction between individual power, trust and control shaped its implementation process. The case study methodology relied on diverse data collection methods including semi-structured interviews, documentary evidence and personal observation. Findings: The authors show that the accounting-based ERP system created an episode of discomfort in the organisation, which facilitated reflexivity and critical reflection by organisation members and led to a re-assessment of ways of thinking pre- and post-dating the implementation of the ERP system. The findings illustrate the entangled relationship between the new accounting-based ERP system and the feelings of trust emerging during organisational change. Practical implications: Although case studies are intrinsically limited in terms of generalisability, the authors' investigation provides practical insights into the management of the needs of trust, ontological security and sources of power experienced by organisation members, since the fulfilment of such needs is the underlying pillar which the success of ERP systems rests upon. Originality/value: This study is one of the first to apply Giddens' (1984, 1990) conceptualisation to examine organisation change caused by the implementation of an accounting-based ERP system in an emerging market economy.